Development and testing of low spatial frequency holographic concentrator elements for collection of solar energy. (October 2017) - Akbari, Hoda; Naydenova, Izabela; Ahmed, Hind; McCormack, Sarah; Martin, Suzanne
Highlights: The potential of photopolymer HOEs is explored for use in solar collection. A combined device was fabricated with symmetrically arranged off axis elements. Testing in a solar simulator, the output current of 12 mm 2 c-Si solar cells is doubled. Abstract: The aim of this research is to use holographically recorded diffractive optical elements (DOEs) recorded in photopolymer in order to effectively collect and concentrate solar radiation. The potential for recording high diffraction efficiency DOEs with a large angular and wavelength range of operation in acrylamide based photopolymer and the optimum recording conditions have been presented in our previous work (Akbari et al., 2014b, 2014a). Theoretical modelling and experimental test are presented which demonstrate that low spatial frequency components, around 300 line pairs/mm, have an appropriate spectral bandwidth, high efficiency and very limited polarization dependence. Pairs of concentrating off-axis lenses are fabricated in photopolymer and arranged to concentrate light on a c-Si cell. The optical recording process is described and discussed. The results from electrical characterization confirm that with the (two) spherical DOEs (each of area 113 mm 2 ) in place, the output current of c-Si solar cells is approximately doubled for the solar cells with area of 12 mm 2 .